2023
DOI: 10.3390/genes14040919
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Regulation of A-to-I RNA Editing on Genes in Parkinson’s Disease

Abstract: Parkinson’s disease (PD) is characterized by dopaminergic neurodegeneration and an abnormal accumulation of α-synuclein aggregates. A number of genetic factors have been shown to increase the risk of PD. Exploring the underlying molecular mechanisms that mediate PD’s transcriptomic diversity can help us understand neurodegenerative pathogenesis. In this study, we identified 9897 A-to-I RNA editing events associated with 6286 genes across 372 PD patients. Of them, 72 RNA editing events altered miRNA binding sit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…ADAR was significantly increased in PPMI PD cases and showed a similar trend in ICICLE-PD (Supplementary Data 11 ). Although ADAR expression levels do not necessarily correlate with editing activity 79 , altered RNA editing has been observed in PD patients’ blood and brain regions 61 , 80 . RNase L degrades circRNAs as a response to viral infection 50 .…”
Section: Discussionmentioning
confidence: 99%
“…ADAR was significantly increased in PPMI PD cases and showed a similar trend in ICICLE-PD (Supplementary Data 11 ). Although ADAR expression levels do not necessarily correlate with editing activity 79 , altered RNA editing has been observed in PD patients’ blood and brain regions 61 , 80 . RNase L degrades circRNAs as a response to viral infection 50 .…”
Section: Discussionmentioning
confidence: 99%
“…ADAR2 and 3 expression was also highest in either prodromal or PD samples depending on whether sexes are combined. Other studies have observed decreased editing frequency [121] and significant differences in ADAR expression [122] in PPMI PD blood; however, these studies did not compare PD males to PD females or PD to prodromal in their analyses and included samples regardless of age; whereas, we chose samples from individuals 65 years or older.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, alterations in ADAR editing at 57 sites correlated with the progression of cognitive symptoms in PD patients [122]. In another study of PPMI whole blood transcriptomes, 72 ADAR editing events were observed that affected miRNA binding, 8 of which may alter the expression of many other genes [121]. Editing within seed regions of miRNA transcripts can potentially change editing targets and cause further dysregulation of gene expression [121].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation